2019
DOI: 10.1002/cche.10145
|View full text |Cite
|
Sign up to set email alerts
|

Higher inositol phosphates and total oxalate of cookies containing fruit by‐products and their influence on calcium, iron, and zinc bioavailability by Caco‐2 cells

Abstract: Background and objectives Fruit by‐products have been used as a strategy to increase the mineral content of cookies. However, to admit functionality in the organism, these minerals must be bioavailable. Therefore, this study aimed to evaluate the effect on the mineral bioavailability (calcium, iron, and zinc) of cookies prepared with partial replacement of wheat flour by fruit by‐products (melon peel, apple endocarp, and pineapple central axis). Findings Cookies containing fruit by‐products presented lower lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Additionally, it increases the resistant starch content in cookies and consequently reduces the starch digestion rate. Toledo et al [ 87 ] included dehydrated and milled pineapple center axis, apple endocarp, and melon peel at concentrations of 5, 10, and 15% in cookies. Pineapple ( Ananas comosus ) is rich in dietary fiber, sugars, vitamins (ascorbic acid, niacin, thiamine), minerals (e.g., potassium, magnesium, copper, manganese), organic acids, volatile ingredients, and bromelain, a proteolytic enzyme that improves digestion [ 88 ].…”
Section: Changes In Chemical Composition and Antioxidant Activitymentioning
confidence: 99%
“…Additionally, it increases the resistant starch content in cookies and consequently reduces the starch digestion rate. Toledo et al [ 87 ] included dehydrated and milled pineapple center axis, apple endocarp, and melon peel at concentrations of 5, 10, and 15% in cookies. Pineapple ( Ananas comosus ) is rich in dietary fiber, sugars, vitamins (ascorbic acid, niacin, thiamine), minerals (e.g., potassium, magnesium, copper, manganese), organic acids, volatile ingredients, and bromelain, a proteolytic enzyme that improves digestion [ 88 ].…”
Section: Changes In Chemical Composition and Antioxidant Activitymentioning
confidence: 99%
“…These micronutrients exert key functions in the macronutrient synthesis and in human physiology [ 4 ]. In our study, as can be observed in Table 2 , the Digestive-type biscuit (A) (containing oatmeal) showed the highest concentration of iron (2.36 mg/100 g).…”
Section: Resultsmentioning
confidence: 99%
“…The next step in our study was to determine the in vitro mineral availability of biscuits. Mineral solubility (%) and dialysis (%) have been widely employed in the literature to study in vitro mineral availability [ 4 , 22 ]. The method consisted of simulating gastrointestinal digestion and measurement of the mineral solubility and dialysis percentages.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations